2005
DOI: 10.1007/s00436-005-1460-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased association of Trypanosoma cruzi with sialoadhesin positive mice macrophages

Abstract: Trypanosoma cruzi is a parasite with large amounts of sialic acid (SA) residues exposed at its surface that seems to be involved in macrophages infection. Some macrophages, present in T. cruzi infected tissues, expresses sialoadhesin (Sn), a receptor that recognizes SA. Thus, the involvement of Sn in the association of T. cruzi to macrophages was investigated. Sn was induced in mice peritoneal macrophages by homologous serum (HS) cultivation. Epimastigotes and trypomastigotes associated more to HS cultured mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…As shown in this report, Siglec-F can also mediate uptake of Neisseria meningitidis expressing sialylated lipooligosaccharides containing the NeuAc␣2-3Gal linkage recognized as a ligand by Siglec-F (3,71). Sn was also found to mediate association of macrophages with Trypanosoma cruzi, a parasite expressing cell surface sialic acids (45), and porcine Sn was shown to mediate the entry of porcine reproductive and respiratory viruses into porcine alveolar macrophages (30,77). Thus, bacteria, parasites, and viruses expressing sialic acids on their cell surfaces are likely to be natural trans ligands of siglec proteins (20,79).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As shown in this report, Siglec-F can also mediate uptake of Neisseria meningitidis expressing sialylated lipooligosaccharides containing the NeuAc␣2-3Gal linkage recognized as a ligand by Siglec-F (3,71). Sn was also found to mediate association of macrophages with Trypanosoma cruzi, a parasite expressing cell surface sialic acids (45), and porcine Sn was shown to mediate the entry of porcine reproductive and respiratory viruses into porcine alveolar macrophages (30,77). Thus, bacteria, parasites, and viruses expressing sialic acids on their cell surfaces are likely to be natural trans ligands of siglec proteins (20,79).…”
Section: Discussionsupporting
confidence: 54%
“…Thus, bacteria, parasites, and viruses expressing sialic acids on their cell surfaces are likely to be natural trans ligands of siglec proteins (20,79). The diversity of interactions of siglec proteins with sialylated pathogens suggests that they may play multiple roles in their interactions with immune cells (8,18,30,38,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siglecs which lack an ITIM domain (such as Siglec-14, 15, and 16) associate with DAP12 via a positively charged amino acid in their transmembrane region to activate receptors through the recruitment of Syk (15,40). Siglec-1, the first discovered member of Siglecs, has been shown to play an important role in sialylated pathogen uptake (17,19,(53)(54)(55), antigen presentation (56,57), lymphocyte proliferation (58), self-tolerance (59,60) and antiviral immune response (47). However, the biological function of Siglec-1 in endotoxin tolerance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion experiments have demonstrated that MZMs are crucial for the entrapment of blood-borne pathogens such as lymphocytic choriomeningitis virus (LCMV) (6), Streptococcus pneumoniae (3), and Listeria monocytogenes (7). MMMs display CD169 (also known as Siglec-1 and recognized by MOMA-1 MAb [8,9]) that recognizes sialylated lipopolysaccharides from Neisseria meningitidis (10) and Campylobacter jejuni (11) and binds to Trypanosoma cruzi (12). MZM populations also play a key role in antigen delivery to B cells (13) and CD4 ϩ T cells (14) and regulate tolerance to apoptotic cells (15,16).…”
mentioning
confidence: 99%